Kashmir Issue During Musharraf Era: A Diplomatic Shift Towards Peace - Shabana Naeem; Shabnam Kausar (Social Science Review Archives, 2025)
In South Asia, Pakistan and India are the next-door states. Since independence, both the states had a long list of historical cum territorial and water disputes. However, Kashmir is the only one issue between Pakistan and India which has always remained both the states at the brink of war. Many democratic and military governments in Pakistan came and went. But none could resolve the issue. Very little work regarding Kashmir issue has been done for the resolution. It is generally said that army was behind the cause to not to solve the Kashmir conflict. But General Pervez Musharraf, after taking office, proved this belief as wrong. Although, Musharraf was a dictator and an army chief but he has worked more for the solution of Kashmir cause than any other political or military leader of Pakistan. Both disputed parties tried to resolve the conflict but the efforts proved fruitless. However, the efforts of Musharraf made the hot environment between two governments, cold up to some extent. Therefore, this study seeks to explore and analyze these efforts for the resolution of Kashmir dispute during Musharraf regime in Pakistan.